2010
DOI: 10.3928/1081597x-20091030-02
|View full text |Cite
|
Sign up to set email alerts
|

LASIK Outcomes Following Multifocal and Monofocal Intraocular Lens Implantation

Abstract: Laser in situ keratomileusis refinement after cataract surgery with monofocal IOL implantation provides a more accurate refractive outcome than after multifocal IOL implantation. Predictability of LASIK correction is limited in hyperopic eyes implanted with multifocal IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
0
27
1
1
Order By: Relevance
“…Today, cataract patients are more demanding and for this reason, cataract surgery is aimed at providing complete and fast visual rehabilitation with minimal postoperative residual refractive errors. 4 In addition to the improvement in biometric devices and IOL power calculations, 5 different IOL designs have been developed and introduced into clinical practice. Some of the designs attempt to improve the optical quality achieved with a standard monofocal IOL, [6][7][8][9][10][11][12] and others attempt to restore not only distance visual function but also intermediate and near vision.…”
Section: Resultsmentioning
confidence: 99%
“…Today, cataract patients are more demanding and for this reason, cataract surgery is aimed at providing complete and fast visual rehabilitation with minimal postoperative residual refractive errors. 4 In addition to the improvement in biometric devices and IOL power calculations, 5 different IOL designs have been developed and introduced into clinical practice. Some of the designs attempt to improve the optical quality achieved with a standard monofocal IOL, [6][7][8][9][10][11][12] and others attempt to restore not only distance visual function but also intermediate and near vision.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Several methods have been proposed in the literature. [10][11][12][13] In our experience, automated refraction has been very helpful in assessing refraction in patients with the Restor SN6AD1 IOL. BissenMiyajima et al 14 found automated refraction with the Restor SN6AD1 IOL to be repeatable and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…14,24,25 One of these advances is the development of more sophisticated IOL designs that provide acceptable retinal image quality at different distances (near, intermediate, and distance). Toric multifocal IOLs were developed to restore visual function at near and distance by compensating for not only defocus but also for astigmatism in eyes with a significant amount of this defect.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Toric IOLs are reported to yield an enhanced visual and refractive effect over that with opposite clear corneal incisions, 5 and new flexible model allow surgeons to use smaller incisions, this providing better control of corneal astigmatism and higher-order aberrations (HOAs). 3,13 However, today's cataract patients are more demanding, and they usually seek total visual rehabilitation 14 and total independence from spectacles, both of which require successful near, intermediate, and distance visual restoration. [14][15][16][17] These requirements were the motivating factor in the development of toric multifocal IOLs.…”
mentioning
confidence: 99%
See 1 more Smart Citation